INTROVERT PERSONALITY: CHALLENGING IN SPEAKING CLASS - Pratiwi, Dyah Sih; Prihatini, Candraning (Journal of English Education and Linguistics, 2023)
The purpose of this research is to find out the challenges of introverted students in practising speaking skills in speaking class. As we know, an introverted personality usually feels shy to speak something in front of a crowded situation. This research investigated the difficulties and the strategies of introverted students in gaining good performance in speaking class. This research used a purposive sampling technique. The sample of this research is 4 students from one of the universities in Lampung. For gaining the introvert sample, this research used Eysenck’s Personality Inventory (EPI). This research is qualitative. The data collecting technique used interviews. The result indicated that there are many challenges in speaking for introverted students. It is because they must face many difficulties to do well performance in speaking class. There are five challenges in speaking class for introverted students namely having a lack of self-confidence, feeling shy, fear of making mistakes, and lack of knowledge. Based on the interview, all introverted students have the same strategy in gaining good performance in speaking class namely well preparation before performing in speaking class. They do a lot of practice before performing in speaking class.